PENGGUNAAN JUMAN & HOQUE METHOD (JHM) PADA PENENTUAN SOLUSI AWAL MASALAH TRANSPORTASI - Andry Nor Indrawan; Pardi Affandi; oni Soesanto (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2021)
Transportation problems are related to the efficient process of distributing goods by a company or industry. The purpose of solving transportation problems is to minimize the costs incurred in the process of distributing goods from several sources (supply) to several destinations (demand). One way to solve transportation problems is to find an initial feasible solution, continued by finding the optimal solution. This research was done by finding an initial feasible solution using the JHM (Juman & Hoque Method) for both the case of solving balanced transportation problems and unbalanced transportation problems. The method has the characteristic in the initial allocation process starting at the cell with the smallest cost in each column as much as the quantity of each demand. In addition, identification of whether the row if occupied or not was done based on the allocation for each row to the quantity of each inventory. This research aimed to explain about solving transportation problems by determining the initial feasible solution using JHM and performing optimality test using potential method. The methods of this research was to identify categories of transportation problems, determine the initial solution using JHM, and test the optimality using potential method. Based on the results of this research, JHM model may be used to solve transportation problems. In the steps of JHM there are explanations of some theorem regarding the selection of the column and row which will be the first to be processed to determine the value of intial solution of transportation problems. The initial solution by using JHM tends to approach the value of optimal solution after test of optimality was done by using the potential method.